2021
DOI: 10.1007/s11135-021-01220-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating the qualitative labour productivity measurement in service industry

Abstract: Over the past two centuries, labour productivity (LP) measured has long been synonymous with productivity measured in manufacturing quantitative features reflecting to its economic dominance. While manufacturing continues to be critical for economic growth, the world has evolved into a service-based economy that is more customer-focused, labourintensive, and interactive in nature. The dominance of quantitative LP measure is not comprehensive enough to capture soft service factors in the service industry, as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Many developing countries made signi cant strides in economic development in the 1990s, accompanied by a shift in labor allocation from agriculture to industry in developing countries and from industry to services in high-income countries, as indicated in the studies by Kinfemichael (2019). However, it is noteworthy that, despite the world evolving into a service-based economy (Amirul et al, 2021), there is still a focus on studies addressing productivity in the manufacturing sector, as seen in the works of Khanna and Sharma (2018a), Zondo (2018) and Singh and Sharma (2020).…”
Section: Bibliometric Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many developing countries made signi cant strides in economic development in the 1990s, accompanied by a shift in labor allocation from agriculture to industry in developing countries and from industry to services in high-income countries, as indicated in the studies by Kinfemichael (2019). However, it is noteworthy that, despite the world evolving into a service-based economy (Amirul et al, 2021), there is still a focus on studies addressing productivity in the manufacturing sector, as seen in the works of Khanna and Sharma (2018a), Zondo (2018) and Singh and Sharma (2020).…”
Section: Bibliometric Resultsmentioning
confidence: 99%
“…However, the last two centuries have shown that the world has evolved into a service-based economy focused on the customer (Amirul et al, 2021). Even though manufacturing remains critical for economic growth, there is a clear need to investigate productivity in a scenario with intangible production, where the value of a service depends directly on customer experience (Günter & Gopp, 2021;Oeij et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that that more investment should be directed to education and training. Numerous scholars [45][46][47] have emphasised that the health of an employee is related to productivity, i.e., healthy people are more productive. Therefore, the impact of investments in improving health on LP is direct.…”
Section: Human Capitalmentioning
confidence: 99%
“…At the end of the pandemic, household spending returned to its pre-pandemic level, together with growing income and correspondingly high levels of household debts. However, the productivity of the service industry (as the efficiency), turning inputs into outputs (Amirul et al 2022(Amirul et al , p. 2854, grew insufficiently.…”
Section: Introductionmentioning
confidence: 99%